Die Geographie der Kreativen Klasse in Deutschland - Michael Fritsch; Michael Stützer (Raumforschung und Raumordnung, 2007)
The article analyses the regional distribution of different categories of creative individuals in Germany. Generally, the share of creative people is higher in cities as compared to the rural areas. The freelancing artists are a kind of exception in this respect; they constitute a relatively high share of the population in some rural areas. A high share of creative people in a region can be explained by a high level of public provisions and a high share of foreign born population, which can be regarded as an indicator of the “openness” in the local milieu. Good employment opportunities have only a relatively weak impact. Regions with a high share of creatives tend to have an above average level of new business formation, a high level of innovation and a relatively high share of employees in high-tech industries.